TELAAH KRITIS TENTANG IMPELEMENTASI RELIGIOSITAS DAN SPIRITUALITAS YANG JUSTRU BERPOTENSI MENIMBULKAN KONFLIK - Yuga Adi Kusuma (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2018)
The implementation of Pancasila in thereformation erahas not been done eagerly. Moreover, Pancasila is not always used as a foundation of government administration practice. This is because globalization has infiltrated Indonesia. Religion is the foundation of every human life, without religion human beings are not able to think instinctively. Besides, Humans will get difficulty to distinguish right and wrong. Unluckily, the incorrect implementation of religiosity and spirituality practices sometimes becomes the trigger of conflict.